Peran Komunikasi Orang Tua dalam Membimbing Anak Saat Belajar pada Masa Pandemi Covid-19 Kelurahan Sei Merbau Kota Tanjung Balai Tahun Pelajaran 2020/2021 - Devi Ananda Panjaitan; Sori Monang; Abdul Karim Batubara (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
The purpose of this study was to find out how the role of parental communication in online learning and to find out the communication barriers of parents in guiding children to learn online in Sei Merbau Village, Tanjung Balai City. This study uses descriptive qualitative research methods. The subjects in this study were elementary school children in Sei Merbau Village, Tanjung Balai City who were undergoing online learning. The object of this research is the role of parental communication. The results of this study concluded that the role of parents in guiding children online has increased as educators, facilitators, motivators, and influencers. Obstacles experienced by parents in guiding their children to learn online are difficult internet network access, the location of buying internet quota is far and the price is quite expensive, it is difficult to divide the time to work and guide children to learn online, the task materials given are many and difficult, and the lack of people's abilities. old in understanding the subject matter.